2020
DOI: 10.52006/main.v3i3.131
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Climate, Job Satisfaction, and Organizational Commitment of Hotel Employees

Abstract: Ethical climate in the workplace has a relationship with job satisfaction and organizational commitment; thus, influencing organizational productivity. This descriptive-correlational study confirmed the relationship between ethical climate, job satisfaction, and hotel employees’ organizational commitment. Using stratified random sampling proportionate allocation, 152 employees from two hotels with the same owner and management were identified as respondents. An adapted-modified survey questionnaire was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Consistent with this study, previous research found a relationship among ethical climate, work engagement and job satisfaction (Menes & Haguisan, 2020;Park & Johnson, 2019).…”
Section: Discussion Of Findingssupporting
confidence: 90%
“…Consistent with this study, previous research found a relationship among ethical climate, work engagement and job satisfaction (Menes & Haguisan, 2020;Park & Johnson, 2019).…”
Section: Discussion Of Findingssupporting
confidence: 90%
“…This study explained the work environment, work-life balance, job attitudes, and productivity through Social Exchange Theory. SET is a significant concept for understanding people's reactions, used in management and related fields (Cropanzano et al, 2017;Menes & Haguisan III, 2020). Blau (1964) asserts that the fundamental premise of the SET is human interaction; therefore, the theory focuses on the social relations and personal ties among the actors that shape the exchange of resources and benefits.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Females reported higher levels of organisational commitment than their male counterparts". [66] examined "the relationship between ethical climate, job satisfaction, and hotel employees' organisational commitment. Using stratified random sampling technique, 152 employees from two hotels with the same owner and management were identified as respondents.…”
Section: Related Studiesmentioning
confidence: 99%